P30-11 Assessment of Disposable of e-vapour products using New Approach Methodologies shows marked reductions in toxicity relative to a cigarette - O. Komini; R. Derr; I. Brandsma; R. Wieczorek; S.J. Pour; E. Trelles-Sticken; C. Kasim; K. Papikinos; M. Stevenson; L. Simms (Toxicology Letters, 2025)

Evolution of immunogenetic components encoding ultralong CDR H3 - Jeannine A. Ott; Christian Mitchell; Morgan Sheppard; Thad C. Deiss; J. M. Cody Horton; Jeremy K. Haakenson; Ruiqi Huang; Abigail R. Kelley; Brian W. Davis; James N. Derr; Vaughn V. Smider; Michael F. Criscitiello (Immunogenetics, 2023)

Corrigendum to Wagner et al .: Natural soil microbes alter flowering phenology and the intensity of selection on flowering time in a wild Arabidopsis relative - Maggie R. Wagner; Derek S. Lundberg; Devin Coleman‐Derr; Susannah Green Tringe; Jeffery L. Dangl; Thomas Mitchell‐Olds (Ecology Letters, 2015)

Natural soil microbes alter flowering phenology and the intensity of selection on flowering time in a wild Arabidopsis relative - Maggie R. Wagner; Derek S. Lundberg; Devin Coleman‐Derr; Susannah G. Tringe; Jeffery L. Dangl; Thomas Mitchell‐Olds (Ecology Letters, 2014)
Plant phenology is known to depend on many different environmental variables, but soil microbial communities have rarely been acknowledged as possible drivers of flowering time. Here, we tested separately the effects of four naturally occurring soil microbiomes and their constituent soil chemistries on flowering phenology and reproductive fitness of Boechera stricta , a wild relative of Arabidopsis. Flowering time was sensitive to both microbes and the abiotic properties of different soils; varying soil microbiota also altered patterns of selection on flowering time. Thus, soil microbes potentially contribute to phenotypic plasticity of flowering time and to differential selection observed between habitats. We also describe a method to dissect the microbiome into single axes of variation that can help identify candidate organisms whose abundance in soil correlates with flowering time. This approach is broadly applicable to search for microbial community members that alter biological characteristics of interest.

The nuclear genome of Brachypodium distachyon: analysis of BAC end sequences - Naxin Huo; Gerard R. Lazo; John P. Vogel; Frank M. You; Yaqin Ma; Daniel M. Hayden; Devin Coleman-Derr; Theresa A. Hill; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Functional & Integrative Genomics, 2008)

EST sequencing and phylogenetic analysis of the model grass Brachypodium distachyon - John P. Vogel; Yong Qiang Gu; Paul Twigg; Gerard R. Lazo; Debbie Laudencia-Chingcuanco; Daniel M. Hayden; Teresa J. Donze; Lindsay A. Vivian; Boryana Stamova; Devin Coleman-Derr (Theoretical and Applied Genetics, 2006)